STUDENTS’ PERCEPTION TOWARDS THEIR SKILL IN READING NOVELS IN WATTPAD APPLICATION - Herlina Herlina; Djunaidi Djunaidi; Yus Vernandes (Esteem Journal of English Education Study Programme, 2023)
The objective of this study was to investigate students' perceptions of their reading skills in novels on the Wattpad application. The research method employed a mixed-method approach, utilising questionnaires, interviews, and documentation to collect data. The population of the study consisted of 11th-grade students at PGRI Senior High School 2 in Palembang. The sample for this study was XI MIPA 1, comprising 36 students from PGRI Senior High School 2 in Palembang. The majority of students (64.7%) fell into the "Good" category based on their responses to the questionnaires. The results of the study revealed that 9 students were classified as "Very Good," 19 students as "Good," 8 students as "Bad," and no students fell into the "Very Bad" category. Based on the students' scores, it can be concluded that the use of the Wattpad application was effective in improving student learning outcomes. This indicates that the Wattpad application was highly beneficial for students, as it provided ample opportunities for them to learn English.